Problems in Writing Passive Voice: A Case Study in the EFL Classes - Jannah, Alda Raudatul; Wilian, Sudirman; Zamzam, Ahmad; Arafiq, Arafiq; Arfah, Hajriana (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2023)
This study addresses EFL students' challenges at a state university in Mataram, Indonesia, in constructing passive voices in the present and past tense. This study was focused on verb tense changes, subject-verb agreement, pronoun usage, and appropriate use of